Comparative study between natural and artificial zeolites as supports for biosorption systems - Tavares, M. T. (2006)
This study aims the definition of a new material that may act as a robust and yet cost effective biosorbent for treatment of wastewater with low concentration of heavy metals. A comparative study was made between two biosorption systems composed of an Arthrobacter viscosus biofilm supported on Cuban natural zeolites and on prepared NaY and NaX, in terms of their ability to retain ionic chromium. The bacterium is able to reduce Cr(VI) to Cr(III) and, only then, this smaller and positive ion may be entrapped in the zeolite cages by ion exchange. The first support was tested in a continuous flow semipacked bed column. The highest removal ratio, 42%, was achieved for initial chromium concentration of 10 mg/L, but the best up-take, 5.5 mg/gzeolite, was obtained for initial concentration of 70 mg/L. Biosorbents prepared with the same biofilm supported in NaY and NaX zeolites were also considered in batch studies, with a typical kinetics of biosorption processes, reaching 20% of initial chromium removal within an initial range of Cr(VI) concentration between 50 and 250 mg/L. These last structures were characterized by spectroscopic methods (FTIR and ICP-AES), surface analysis (DRX) and thermal analysis (TGA). All these techniques indicated that the biosorption process does not modify the morphology and structure of the FAU-zeolites.